Perancangan Buku Cerita Bergambar Tentang Bullying Pada Anak - anak Berjudul Sepeda Tua Dan Semangat Si Made Dengan Teknologi Augmented Reality Kolaborasi Karakter Blelozz di Madeblez Studio - Hendra, I Made; Artawan, Cokorda Alit; Negara, I Nengah Sudika (Program Studi Desain Komunikasi Visual, 2024)
Bullying is a negative behavior carried out by a stronger party against a weaker one, using or not using tools, with the aim of causing them to feel pressured, both physically and emotionally (M. Miftahuddin Al Amin, 2018:12). Bullying behavior has become a common occurrence among children, resulting in long-term psychological impacts on individuals. There is a need for a medium that can be used to educate about the effects of bullying and how to cope with it. The illustrated storybook